(untitled) (Research, Society and Development, 2022)
It is evident that the use of mobile technologies as tools that facilitate the development of experimental activities has gained prominence in recent decades, being an intermediate instrument in the teaching-learning process. Therefore, this work sought to score and tabulate the contributions of the "Virtual Physics Laboratory" application as a Physics teaching tool with students of the 1st year of high school. However, to answer the question made in the current work, the following script was prepared: 1) Run the application in the classroom, at the place where these students study; 2) To verify how the students’ learning would be when using the application in the classroom, first through observation and then with the application of a questionnaire, and thus, identify how the students dealt with the use of the application in practical Physics classes 3) To analyze the students’ opinion about the use of the “Virtual Physics Laboratory” application, through objective questions answered at the time of execution of the application in the Physics class. In this sense, data collection was based on the development of graphs to clearly show the importance of this tool for students learning, a questionnaire consisting of three questions, all made for the 30 students, and applied by the Pibidian students and the assistance from the PIBID regional coordinator. At the end of data collection, analyzes were performed through the three graphs, where each answer was represented.